Partição de nicho e tolerância termal de formigas arbóreas em uma savana Neotropical - Zuanon, Lino Abdelnour (2018)
Niche partitioning is among the most frequent mechanisms invoked to explain diversity at local scales. However, the importance of niche partitioning for ant communities seems to be contextual. In communities with temporal and spatial niche partitioning, arboreal ant species are exposed to different environmental conditions, such as temperature. Since the machinery that defines the thermal limits is highly expensive, adaptation by species active in different periods or using different microhabitats is expected. I studied the spatial, trophic and temporal niche in an arboreal ant community in a cerrado savanna and determined the thermal tolerance of species active during different hours of the day. I sampled ants in 90 Caryocar brasiliensi trees at three different periods: morning (06:00-08:00am), afternoon (12:00-02:00pm) and night (11:00pm-01:00am), and recorded the air temperature during all sampling events. In order to determine the trophic niche of arboreal ants, eight baits of four types (sugar, urine, olive oil and dead insects) were randomly placed in different branches of each sampled tree. The thermal tolerance (maximum temperature tolerated by ant workers before dying) of the most common ant species was determined in the laboratory using a dry heat bath. The analyses of the most frequent species showed significant temporal partitioning of day time and a high overlap in the use of trophic resources (bait types). Also, a segregated spatial pattern of co-occurrence at the scale of trees, with a tendency for pairs of species with greater temporal overlap to be more spatially segregated than pairs with less temporal overlap. There was also a positive relation between mean temperature of activity and thermal tolerance of species, which indicates that is also possible that physiological constrains can be more important than competition in determining temporal segregation. I found niche partitioning to be a relevant mechanism for the arboreal ants at the studied community. Even if species highly overlap in their diet, they avoid competition and maintain coexistence by occupying different trees or foraging at different periods of the day.